1996
DOI: 10.1039/cc9960002753
|View full text |Cite
|
Sign up to set email alerts
|

1-Ethyl-3-methylimidazolium halogenoaluminate melts as reaction media for the Friedel–Crafts acylation of ferrocene

Abstract: Ionic liquid mediated Friedel-Crafts acylation of the organometallic complex ferrocene can be performed in l-ethyl-3-methylimidazolium halogenoaluminate melts, Et-MeimI-A1C13, as well as in the liquid clathrate formed upon addition of an excess of toluene to EtMeimI-A1Cl3 affording solely the monoacylated product acetylcyclopentadienyl (cyclo-pentadienyl)iron(II) in good to excellent yields under the appropriate conditions.Use of low-melting ionic liquids composed of an organic chloride and aluminium chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 10 publications
0
50
0
Order By: Relevance
“…Among the key applications of liquid-ionic liquid biphasic catalysis with acidic chloroaluminate ILs are Friedel-Crafts alkylation [26][27][28][29], Friedel-Crafts acylation [30][31][32] and carbonylation reactions [33][34][35]. Other important acid catalyzed reactions that have been successfully carried out in form of liquid-ionic liquid biphasic catalysis include oligomerization [36], cracking [37,38] and refinery alkylation reactions [39][40][41].…”
Section: Liquid-ionic Liquid Biphasic Catalysis Usingmentioning
confidence: 99%
“…Among the key applications of liquid-ionic liquid biphasic catalysis with acidic chloroaluminate ILs are Friedel-Crafts alkylation [26][27][28][29], Friedel-Crafts acylation [30][31][32] and carbonylation reactions [33][34][35]. Other important acid catalyzed reactions that have been successfully carried out in form of liquid-ionic liquid biphasic catalysis include oligomerization [36], cracking [37,38] and refinery alkylation reactions [39][40][41].…”
Section: Liquid-ionic Liquid Biphasic Catalysis Usingmentioning
confidence: 99%
“…[9][10][11][12] These solvents, which have been the subject of a number of reviews, [13][14][15][16][17][18][19][20] have also received much popular attention. [21][22][23][24][25][26][27] To give a sense of the scope for these solvents, it is worth mentioning that recent studies have shown that ambient-temperature ionic liquids can be used as media for a wide range of chemical reactions, including hydrodimerization, 28 hydrogenation, [29][30][31][32][33][34] dimerization, 35 polymerization, 36 alkylation, 37 FriedelCrafts reactions, [38][39][40][41] Heck coupling, 42,43 the DielsAlder reaction [44][45][46] and enzymatic catalysis of biotransformations. 47 As part of a programme aimed at understanding more about the nature of these ambient-temperature ionic liquids, and how they compare with conventional solvents, we have undertaken a study of their polarity using the solvatochromic dye Nile Red (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, when both dipole and quadrupole moments are present in an aromatic compound, they have an antagonistic effect, reducing the solubility in the IL (Shimizu et al, 2009). Up to now, such liquid clathrates or IL-biphases have been used in the fields of organic syntheses (Boxwell et al, 2002;Clavier et al, 2008;DeCastro et al, 2000;Surette et al, 1996), polymerization (Csihony et al, 2002), separations of aromatics from hydrocarbons (Arce et al, 2007;Selvan et al, 2000) and so on. Holbrey et al obtained crystalline [C 1 mim][PF 6 ]·0.5C 6 H 6 by cooling the lower phase of the [C 1 mim][PF 6 ]−C 6 H 6 system to room temperature.…”
Section: Inclusion Of Aromatic Compounds In Ionic Liquidsmentioning
confidence: 99%